Diagnosing Parkinson Disease. Issue 4 (August 2016) - Hess, Christopher W.; Okun, Michael S.
Abstract : ABSTRACT: Purpose of Review: While establishing the diagnosis of Parkinson disease (PD) can be straightforward, it can be challenging in some patients, even for the experienced neurologist. The misdiagnosis rate ranges from 10% to 20% or greater depending on clinician experience. Recent Findings: Despite promise in the search for a biomarker that can establish the presence of PD and act as a marker of its progression, the diagnosis of PD continues to be based on clinical examination. Core criteria, exclusion criteria, and supportive criteria have been developed to aid the clinician in establishing the diagnosis. Nonmotor symptoms of PD are usually present at the time of diagnosis, may precede motor symptoms, and should be specifically sought during evaluation. Ancillary testing can be appropriate, but its indications and utility must be clearly understood. Summary: The diagnosis of PD requires the recognition of the core features of PD and the differentiation of its clinical presentation from other entities with similar and potentially overlapping symptoms. A careful history and examination guided by clinical diagnostic criteria will usually establish the diagnosis of PD or uncover red flags for the possibilities of other diagnoses. Appropriate selection and interpretation of ancillary testing is critical to avoid misdiagnosis and unnecessary tests.